Spatially Structured Environmental Variation Plays a Prominent Role on the Biodiversity of Freshwater Macrophytes Across China - Zhang, Min; García Molinos, Jorge; Su, Guohuan; Zhang, Huan; Xu, Jun (Frontiers in Plant Science, 2019)
Large-scale diversity patterns are generated by different non-mutually exclusive mechanisms. Understanding of multiple facets of diversity and their determinants in the freshwater realm remains limited compared to terrestrial environments. Here, we analyze the relative contribution of environmental gradients and spatial variables to patterns of taxonomic, phylogenetic, and functional diversity in macrpohyte assemblages across 214 Chinese watersheds. We found extremely high spatial congruence among most aspects of biodiversity, with some important exceptions. Variation partitioning was used to examine how much variation in macrophyte biodiversity was explained by environmental and spatial variables. All diversity facets were best explained by the selected spatially structured environmental variables, not the pure environment effect, implying that macrophyte are taxonomically, phylogenetically, and functionally clustered in space, which might be the result of environmental and/or evolutionary forces. Along with the potent effects of dispersal limitations, macrophytes seem to face general dispersal limitations although they are often recognized as good dispersers.